What Population and What Question? - Rice, Marnie E. (Canadian journal of criminology and criminal justice, 2006)
The article reflects on the high rate of sexual recidivism reported on the article published by Ron Langevin and fellow journalist. The authors criticized the study's shortcomings. It questioned the population discussed in the article and the overestimation on recidivism. It also argued the definition of recidivism and the methodological bias. Data gathered on recidivism are said to be incomplete and so are the judgment made on the article. The author believes that Cheryl Marie Webster's criticism about the invalid approach and unconventional way of measuring recidivism of Ron Langevin and fellow journalists are correct